PENGARUH VARIASI MEDIA PENGGORENGAN TERHADAP PENGOLAHAN ABON IKAN BETOK (Anabes Testidineus) - Muflih, Achmad; Yanto, Subari; Lahming, Lahming (Universitas Negeri Makassar, 2017)
The aimed of study is to determine the effect of variations of frying media on processing the abon of betok fish and the acceptance of panelist on abon betok fish has resul. This study used Completely Randomized Design with palm oil treatment (double filtering) and coconut oil (cocos nucifera). The parameters which observed were water content, ash,Â protein content, crude fiber and hedonic quality are color, aroma, flavor and texture. Based on the best proximate test results was abon which using used ordinary palm frying media. The result of organoleptic test the showed the pleasure of panelist's level towardÂ abon betok fish which was processed by using ordinary coconut oil that had color value about 6.67%, 7.20% aroma, 6.73% flavor, and texture 6,19%.